Identification and Functional Testing of Novel Interacting Protein Partners for the Stress Sensors Wsc1p and Mid2p of Saccharomyces cerevisiae. Issue 4 (1st April 2019) - Santiago-Cartagena, Ednalise; González-Crespo, Sahily; Vélez, Vladimir; Martínez, Nelson; Snider, Jamie; Jessulat, Matthew; Aoki, Hiroyuki; Minic, Zoran; Akamine, Pearl; Mejías, Inoushka; Pérez, Luis M; Rymond, Brian C; et al.
Abstract: Wsc1p and Mid2p are transmembrane signaling proteins of cell wall stress in the budding yeast Saccharomyces cerevisiae . When an environmental stress compromises cell wall integrity, they activate a cell response through the Cell Wall Integrity (CWI) pathway. Studies have shown that the cytoplasmic domain of Wsc1p initiates the CWI signaling cascade by interacting with Rom2p, a Rho1 -GDP-GTP exchange factor. Binding of Rom2p to the cytoplasmic tail of Wsc1p requires dephosphorylation of specific serine residues but the mechanism by which the sensor is dephosphorylated and how it subsequently interacts with Rom2p remains unclear. We hypothesize that Wsc1p and Mid2p must be physically associated with interacting proteins other than Rom2p that facilitate its interaction and regulate the activation of CWI pathway. To address this, a cDNA plasmid library of yeast proteins was expressed in bait strains bearing membrane yeast two-hybrid (MYTH) reporter modules of Wsc1p and Mid2p, and their interacting preys were recovered and sequenced. 14 previously unreported interactors were confirmed for Wsc1p and 29 for Mid2p . The interactors' functionality were assessed by cell growth assays and CWI pathway activation by western blot analysis of Slt2p /Mpk1p phosphorylation in null mutants of each interactor under defined stress conditions. The susceptibility of these strains to different stresses were tested against antifungal agents and chemicals. This study reports important novel protein interactions of Wsc1p and Mid2p that are associated with the cellular response to oxidative stress induced by Hydrogen Peroxide and cell wall stress induced by Caspofungin.